Dapagliflozin cost-effectiveness analysis in heart failure patients in Egypt. (31st December 2022) - Abdelhamid, Magdy; Elsisi, Gihan Hamdy; Seyam, Ahmed; Shafie, Ahmed; Kirollos, Mary; Emad, Sandy; Mansy, Shady; Sobhy, Mohamed
Abstract: Aims: In Egypt, cardiovascular (CV) diseases are not only the cause of 33% of disability-adjusted life years but are also a leading cause of death. This study aimed to evaluate dapagliflozin's cost-effectiveness as an add-on to the standard of care (SOC) for the treatment of heart failure with reduced ejection fraction (HF-rEF) from the Egyptian healthcare system perspective. Materials and methods: A state transition model was utilized to assess the cost-effectiveness of dapagliflozin as an add-on to the SOC and a cost-minimization analysis was performed to compare dapagliflozin to sacubitril/valsartan, as they have had similar efficacy. Patients were stratified into four health states using the KCCQ-TSS, in addition to a CV and non-CV mortality health states. Urgent heart failure (HF) visits and hospitalizations were captured as transient states. Clinical parameters and baseline characteristics were based on the DAPA-HF trial, utility scores were extracted from published articles, and costs were derived from the Universal Health Insurance Authority national database. Deterministic and probabilistic sensitivity analyses were performed. Results: The treatment costs of HF-rEF patients receiving dapagliflozin compared to SOC are 47, 901EGP ($10, 550) and 34, 377EGP ($7, 572), respectively. The quality-adjusted life-years (QALYs) of dapagliflozin compared to SOC are 4.57 and 4.20, respectively. This resulted in an incremental cost per effectiveness ratio (ICER) of 36, 449EGP ($8, 028) per QALY gained over the lifetime horizon, suggesting this is cost-effective. Results of the cost-minimization analysis showed cost savings where the annual costs of dapagliflozin vs. sacubitril/valsartan are 10, 914EGP ($2, 404) and 32, 242EGP ($7, 101), respectively. Conclusion: Dapagliflozin was found to be a highly cost-effective and cost-saving medication when compared to SOC and sacubitril/valsartan, respectively, in the treatment of HF-rEF from Egyptian healthcare system perspective. The ICER was below the willingness-to-pay threshold because dapagliflozin improved outcomes (less frequent hospitalization and mortality).